Soft skill learning device for elementary school students through the learning of physical education in merdeka curriculum - Muarifin Muarifin (CV Rezki Media, 2022)
The purpose of this study was to find out the initial observations about the Soft Skill Needs for Elementary School Students through Learning Physical Education, Sports and Health in the “Merdeka Belajar” Curriculum. Subjects were 8 Physical Education, Sports and Health Teachers who filled out a softskill analysis questionnaire. The results show that Physical Education teachers still experience obstacles and difficulties in compiling and designing learning or teaching modules that emphasize aspects of soft skills. The conclusion is that Physical Education teachers have difficulty and do not know in compiling or making learning tools or what is currently known is teaching modules that emphasize soft skill elements.